2016
DOI: 10.4236/wjet.2016.44057
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Reinforced Concrete Columns Strengthened with Ferrocement under Compression Conditions: Experimental Approach

Abstract: This paper reports a study based upon experimental investigation which aims to assess the behaviour of reinforced concrete columns strengthened with a new configuration of steel wire mesh as part of ferrocement layer under the action of axial compression loads. Square and circular small scale columns with three different slenderness ratios of 5, 6.7 and 10 were adopted. A comprehensive experimental progarmme was then running to measure the load capacity and both lateral and vertical displacements. The failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Two groups of the hybrid fibres were used in the ECC ; the first incorporated 0.5% steel and 0.5% polypropylene fibres, and the second incorporated 1% steel and 0.5% polypropylene fibres. The former fibre percentages were recommended by previous studies [1,5].…”
Section: Selection Of the Concrete MIXmentioning
confidence: 99%
See 2 more Smart Citations
“…Two groups of the hybrid fibres were used in the ECC ; the first incorporated 0.5% steel and 0.5% polypropylene fibres, and the second incorporated 1% steel and 0.5% polypropylene fibres. The former fibre percentages were recommended by previous studies [1,5].…”
Section: Selection Of the Concrete MIXmentioning
confidence: 99%
“…1 Table 3. The calculated and measured results of load carrying capacity for the eccentric loaded columns (1) Where is the approximate value of ultimate load in biaxial bending with eccentricities and ; 0 is the ultimate load when only eccentricity is present;…”
Section: Table 2 the Values Of Compressive Strengths For Different Cmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the square-shaped columns give more ability to carry out the axial compression load over the circular column and the reference columns, considering the slenderness ratio. Adopting wire mesh to form the ferrocement layers as a reinforcement is an effective technique to increase the load carrying capacity of the column [8]. Effective confinement of concrete in a column using square ferrocement jacketing cannot be provided by single or double layers of mesh and mortar only [9].…”
Section: Ferrocementmentioning
confidence: 99%
“…Numerous experimental and numerical studies were performed to evaluate the performance of strengthening schemes on the behaviour of RC columns exposed to high temperatures. Significant studies have been investigated the influence of utilising ferrocement confinement in strengthening and repairingRCcolumns [2][3][4][5][6][7][8][9][10][11]. In general, the results indicated that the strength and deformability of RCcolumnscould be enhanced by encased ferrocement.…”
Section: Introductionmentioning
confidence: 99%